Human papillomavirus infection and immunologic riskof uterine cervical cancer - Cervantes, Jorge (2015)
Uterine cervical cancer is becoming an important Public Health problem in developing countries. There is a role of certain human papillomavirus genotypes (HPV) in the pathogenesis of cervical cancer The risk of cervical cancer depends on the HPV type and on the population, and both viral and host factors are necessary for the development of pre?cancerous lesions and finally cervical cancer.